Measurement and simulation of the suspension velocity of flax threshing material using CFD-DEM - Dai, Fei; Guo, Wenjuan; Song, Xuefeng; Shi, Ruijie; Qu, Jiangfei; Zhao, Wuyun (International Journal of Agricultural and Biological Engineering, 2021)
In order to explore the aerodynamics characteristics of flax threshing material, and accurately obtain the movement trajectory of the material of each component in air-screen cleaning, the suspension velocities of flax grains, capsules, short stalks and capsule husks at different stages were measured by means of the suspension velocity device. The experimental results showed that the suspension velocity range was 4.55-8.64 m/s for flax grains, 6.46-10.90 m/s for flax capsules, 3.23-7.75 m/s for flax short stalks, and 1.06-4.21 m/s for flax capsule shells. Based on the experimental results, the overall interval distribution of each component of flax threshing material and the separation characteristics were discussed and the discrete element model of each component of the flax threshing material was established. Through simulation measurement of angle of repose of the material and the sliding friction angle with steel, the reliability of the established model was verified. The gas-solid coupling method was used to simulate the suspension velocity of each component of the flax threshing material, and the suspension velocity of the four components of flax threshing material was obtained. The simulation measurement results were within the actual measurement range, showing that the test results were basically in line with the simulation results. The simulation on the suspension velocity of different components of flax threshing material based on gas-solid coupling had high precision degree. Therefore, the feasibility of the suspension velocity of the flax threshing material measured in the simulation test based on CFD-DEM coupling was verified. Keywords: flax, threshing material, suspension velocity, CFD-DEM, numerical simulation DOI: 10.25165/j.ijabe.20211405.6651 Citation: Dai F, Guo W J, Song X F, Shi R J, Qu J F, Zhao W Y. Measurement and simulation of the suspension velocity of flax threshing material using CFD-DEM. Int J Agric & Biol Eng, 2021; 14(5): 230–237.